2013
DOI: 10.1126/science.1239275
|View full text |Cite
|
Sign up to set email alerts
|

A Gut Lipid Messenger Links Excess Dietary Fat to Dopamine Deficiency

Abstract: Excessive intake of dietary fats leads to diminished brain dopaminergic function. It has been proposed that dopamine deficiency exacerbates obesity by provoking compensatory overfeeding as one way to restore reward sensitivity. However, the physiological mechanisms linking prolonged high-fat intake to dopamine deficiency remain elusive. We show that administering oleoylethanolamine, a gastrointestinal lipid messenger whose synthesis is suppressed after prolonged high-fat exposure, is sufficient to restore gut-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
328
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(348 citation statements)
references
References 34 publications
(36 reference statements)
18
328
0
2
Order By: Relevance
“…2001; Fu et al 2003; Tellez et al. 2013). In support of this idea, OEA activated vagal afferent neurons in cultures of nodose ganglia neurons (Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…2001; Fu et al 2003; Tellez et al. 2013). In support of this idea, OEA activated vagal afferent neurons in cultures of nodose ganglia neurons (Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also found that OEA decreased neuronal activity within the nucleus accumbens, as suggested by the low expression of c-Fos in both HDC-KO and WT mice. Although in this context we did not investigate this aspect further, it is interesting that OEA restores gut-stimulated dopamine release in the striatum of high-fat-fed rats increasing the reward value of unpalatable, yet healthier food (38). As brain histamine signaling in the PVN seems to be involved in the acute effects of OEA on food consumption, we expected OEA to increase brain histamine release.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in obese patients, obesity might be exacerbated by a reduction in the ability of post-ingestive nutrients to activate dopamine signalling. This has been suggested by the link between gut-derived signals and dopamine in high-fat fed mice [61]. Finally, decoupling of taste from nutritional content may also be involved in behavioural and metabolic disturbances.…”
Section: Implications For Obesity and Human Feeding Behaviourmentioning
confidence: 99%
“…This effect was mediated by reduced release of the gut-derived satiety factor, oleoylethanolamine (OEA) [61]. Thus, one potential mechanism underlying obesity might be the inability of postingestive signals such as OEA to activate dopamine signalling and induce satiety.…”
Section: Post-ingestive Infusionsmentioning
confidence: 99%
See 1 more Smart Citation